Simulasi Tinggi Gelombang Laut Signifikan di Selat Makassar Pada Bulan Januari-Februari 2016 - Muhammad Riza; Qori Fajar Hermawan; Zetsaona Sihotang; Nanda Khoirunisa; Idris Mandang (Program Studi Teknik Geofisika FITK UHO, 2023)
Knowledge of the characteristics of sea waves is very important for many maritime fields such as shipping safety, offshore industry, coastal area development, defense, and ship design. As the largest maritime country in the world, Indonesia is vulnerable to high sea waves. BMKG adopts the third generation wave model, namely WAVEWATCH-III which was developed by NOAA, USA. This model is used to predict the height and direction of sea waves in Indonesian waters. The purpose of this study is to determine the characteristics of the results of the WAVEWATCH-III wave model in the Makassar Strait. In January-February 2016 significant sea wave heights ranged from 0 m to 1.5 m and the direction of the waves came from the northeast in the Makassar Strait. Significant wave heights in January-February 2016 were not at a level that endangered shipping lanes in the Makassar Strait area. Keywords: Ocean Waves, Makassar Strait, Wave Model.